Properties and reactivity of μ‑nitrido‑bridged dimetal porphyrinoid complexes: how does ruthenium compare to iron? - Muhammad Qadri Effendy Mubarak; Alexander B. Sorokin; Sam P. de Visser (Springer, 2024)
Methane hydroxylation by metal-oxo oxidants is one of the Holy Grails in biomimetic and biotechnological chemistry. The only enzymes known to perform this reaction in Nature are iron-containing soluble methane monooxygenase and copper-containing particulate methane monooxygenase. Furthermore, few biomimetic iron-containing oxidants have been designed that can hydroxylate methane efficiently. Recent studies reported that μ-nitrido-bridged diiron(IV)-oxo porphyrin and phth-alocyanine complexes hydroxylate methane to methanol efficiently. To find out whether the reaction rates are enhanced by replacing iron by ruthenium, we performed a detailed computational study. Our work shows that the μ-nitrido-bridged diruthenium(IV)-oxo reacts with methane via hydrogen atom abstraction barriers that are considerably lower in energy (by about 5 kcal mol‒1) as compared to the analogous diiron(IV)-oxo complex. An analysis of the electronic structure implicates similar spin and charge distributions for the diiron(IV)-oxo and diruthenium(IV)-oxo complexes, but the strength of the O‒H bond formed during the reaction is much stronger for the latter. As such a larger hydrogen atom abstraction driving force for the Ru complex than for the Fe complex is found, which should result in higher reactivity in the oxidation of methane.